(untitled) (Global Journal of Medical Research, 2023)
Objective To assess the diagnostic performance and yield of fine needle aspiration cytology FNAC of thyroid nodules Design Retrospective study Setting Archives of the Pathology Department at King Saud University Medical City Saudi Arabia between January 2016 and May 2021 Subjects Overall 3867 FNAC results from 2442 patients with thyroid nodules with available histopathological follow-up material were included in this study Intervention Comparison of the FNAC diagnostic performance with the final histopathological diagnoses